Hegemony of Masculinity in Eka Kurniawan's Seperti Dendam, Rindu Harus Dibayar Tuntas - Salsabila, Cruizita Az-zahra; Adji, Muhamad; Hamid, Abdul (Balai Bahasa Kalimantan Tengah, 2025)
This article aims to discuss the representation of masculinity and the responses of male characters to societal demands for masculine characteristics in Eka Kurniawan's novel Seperti Dendam, Rindu Harus Dibayar Tuntas. The article utilizes R.W. Connell's theory of hegemonic masculinity and Antonio Gramsci’s theory of hegemony to explore how masculinity is represented in the narrative and how male characters respond to the social construction of ideal masculinity. It identifies key themes related to masculinity and male character responses, as well as the interactions between characters and the internal conflicts they experience. The findings reveal that the representation of masculinity in the novel reflects the 1980s era, characterized by authoritative behaviour, sexual aggression, and the use of violence as a form of manliness. The conflict between masculinity expectations and individual emotional needs drives male characters to exhibit responses that reflect both resistance and affirmation of societal masculinity stereotypes.